-8*v-2=-6(v-1)

Simple and best practice solution for -8*v-2=-6(v-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8*v-2=-6(v-1) equation:


Simplifying
-8v + -2 = -6(v + -1)

Reorder the terms:
-2 + -8v = -6(v + -1)

Reorder the terms:
-2 + -8v = -6(-1 + v)
-2 + -8v = (-1 * -6 + v * -6)
-2 + -8v = (6 + -6v)

Solving
-2 + -8v = 6 + -6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '6v' to each side of the equation.
-2 + -8v + 6v = 6 + -6v + 6v

Combine like terms: -8v + 6v = -2v
-2 + -2v = 6 + -6v + 6v

Combine like terms: -6v + 6v = 0
-2 + -2v = 6 + 0
-2 + -2v = 6

Add '2' to each side of the equation.
-2 + 2 + -2v = 6 + 2

Combine like terms: -2 + 2 = 0
0 + -2v = 6 + 2
-2v = 6 + 2

Combine like terms: 6 + 2 = 8
-2v = 8

Divide each side by '-2'.
v = -4

Simplifying
v = -4

See similar equations:

| .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 |

Equations solver categories